AN INVESTIGATION INTO THE DISPARITY BETWEEN LECTURERS' USE OF TECHNOLOGY IN TEACHING AND STUDENTS' DIGITAL COMPETENCE: A CROSS-SECTIONAL CASE STUDY OF THE BACHELOR OF APPLIED SCIENCE PROGRAM AT MANGOSUTHU UNIVERSITY OF TECHNOLOGY. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background This study investigates the disparity in technological proficiency between lecturers and students in the Bachelor of Applied Science program at Mangosuthu University of Technology (MUT), focusing on its impact on teaching effectiveness and student engagement. Methods A mixed-methods approach was employed, combining surveys and semi-structured interviews. The study included 80 participants, 60 students, and 20 lecturers from the Faculty of Natural Sciences. It examined levels of digital literacy, access to technology, and perceptions of technology-enhanced learning. Quantitative data were analyzed using descriptive statistics, while qualitative responses underwent thematic analysis. Results Findings revealed a significant digital proficiency gap between students and lecturers. Most students (60%) were aged 18–24, with 85% reporting high familiarity with digital tools such as Google Workspace, Moodle, and mobile apps. In contrast, lecturers, predominantly aged 45 and above, showed limited digital confidence, with only 40% comfortable using tools beyond PowerPoint and email. Students primarily accessed learning content via mobile devices, while lecturers favored traditional teaching methods with minimal technology integration. Qualitative insights highlighted limited training and institutional support as key barriers for lecturers, while students expressed frustration with the lack of interactive digital learning. These results point to a generational and infrastructural divide that hampers effective technology-enhanced teaching. Conclusion The disparity in digital competence between lecturers and students impedes the successful implementation of digital learning within the program. Bridging this gap is essential for inclusive, effective, and future-ready higher education. Recommendations MUT should introduce compulsory digital literacy training for lecturers, strengthen technical support systems, and adopt blended learning strategies. Further research is recommended to explore policy-level reforms that can drive sustainable digital integration in higher education.